Impact of epiphora on modified ocular surface disease index questionnaire - Ercan, Zeynep Eylül (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Epiphora (excessive tear production) is a major ocular disturbance, especially among middle aged and older patients. It can be due to lacrimal drainage malfunction of any kind. The aim of this study was to evaluate the effects of epiphora with good passage on lacrimal irrigation on a modified Ocular Surface Disease Index (OSDI) questionnaire. A total of 101 patients (53 males/ 48 females) were included in the study. The modified OSDI questionnaire had 11 items concerning ocular symptoms that affects daily activities. The relationships between the questionnaire score for each question and the clinical features included age, gender and previous cataract surgery. The most affected activities according to modified OSDI were watching television, windy conditions and cold weather (average means of 3.36 + 0.82, 3.42 +±0.86 and 3.40 +±0.88, respectively). Epiphora was found to have a statistically significant effect on daily life, all except with regard to interpersonal relations (p=0.493) with increasing age. Women were found to be experiencing more eye grittiness (p=0.0001), getting more affected during reading (p=0.027), at hot/dry climates (p=0.0001) and believed epiphora has an important impact on interpersonal relations and general happiness (p<0.0001). Pseudophakic patients also showed statistically significant increase of discomfort in daily life questions in 7 of the 11 questions (p<0.0001). This study showed the subjective epiphora related symptoms impact on a modified OSDI. This questionnaire was easy to manage and quick to complete while showing similar results to those that were specifically designed for epiphora with nasolacrimal obstruction. We believe that the results could help to improve overall therapeutic management of patients with epiphora.